ChemInform Abstract: Preparation of the Monoacylates of 2‐Substituted (Z)‐But‐2‐ene‐1, 4‐diols Using Porcine Pancreas Lipase. Issue 29 (29th June 2016) - Kawashima, Yuya; Ezawa, Tetsuya; Harada, Taisuke; Noguchi, Takuya; Kawasaki, Masashi; Kirihara, Masayuki; Imai, Nobuyuki
Abstract: Regioselective acylations of (Z)‐but‐2‐ene‐1, 4‐diols can be performed with 10 equivalents of vinyl acetate in the presence of porcine pancreas lipase.